Reform momentum and its impact on Greek growth - Alessio Terzi (Bruegel, 2015)
Greece has an imperfect track-record of structural reform implementation. However, the poor growth outcome of the Greek programmes is also a consequence of the timing and composition of reforms, which were not optimally geared towards a speedy transition to a new growth model based on the private sector. While the main responsibility for this lies with the Greek authorities, international institutions share the responsibility for the poor growth-enhancing effect of reforms. In the current context, further structural reform efforts should be mainly targeted at supporting Greece's speedy return to solid growth rates. This is not only because poverty and unemployment have reached very high levels, but also for political economy reasons: reforms must quickly be seen to be working in order to buttress the consensus in favour of reform. Further efforts should be made to improve Greece's business environment and to liberalise product markets, in addition to shifting taxation away from labour and towards consumption. Reforms to improve the quality of institutions should continue and are very much needed in the Greek setting, while taking into account that their demanding implementation might use up administrative capacity and their impact on growth will only be seen over long time horizons.
Keywords: 330